Characteristics Of Acute Appendicitis Patients In Muhammadiyah University General Hospital Malang 2015-2018 Period - Sulaiman Rasjid; Mochamad Aleq Sander (Saintika Medika : Jurnal Ilmu Kesehatan dan Kedokteran Keluarga, 2023)
This disease can occur at any age but generally occurs in young adults and adolescents, namely at the age of 10-30 years, and the highest incidence is in the 20-30 year age group. One in 15 people has had acute appendicitis in their lifetime. The highest incidence is in men aged 10-14 years and women aged 15-19 years. Appendicitis is rare in infants and children under two years. This type of research is descriptive retrospective. Samples were all patients diagnosed with acute appendicitis who met the inclusion criteria at the General Hospital of Muhammadiyah Malang University. Independent variables: acute appendicitis and dependent variable: medical record status containing sample characteristics, clinical diagnosis, and surgical technique. Data analysis was done by tabulating with descriptive tables. The study results obtained 258 patients with a diagnosis of acute appendicitis, divided into 137 people with a simple appendectomy surgery technique and 121 people with a laparoscopic appendectomy surgery technique. The conclusion shows that the age of most patients with acute appendicitis is 11-30 years. The most gender is female, the most patient service status is BPJS, and the most surgical technique is simple appendectomy.